EKSEKUTORIAL PUTUSAN PEMBATALAN MEREK TERDAFTAR - Eko Yuliyanto (Faculty of Law, Universitas Lampung, 2020)
Brand cancellation is implemented through the delete list of the brands, it has brought legal consequences such the expire protection by the state. However, it is still leave some problems if the brand cancellation not accompanied by concrete actions such of a ban on re-use of the brand that has been canceled.The paper will focus on the analysis of judges' consideration in making the decision to cancel the registered brand (case study of decision No. 85 PK / Pdt.Sus-HKI / 2015), as well as an analysis of the execution of the decision to revoke registered brand (case study of decision No. 85 PK / Pdt.Sus -HKI / 2015). The method used is normative legal research. The results of the study showed that the legal basis by the Judges had accommodated all the substance of the juridical reason for the cancellation of the brand Cap Kaki Tiga by referring the provisions of Article 6 paragraph (3) letter b of Trademark Law (currently regulated in Article 21 Paragraph (2) letter b of the Trademark and Geographical Indications Law).Furthermore, an executorial decision regarding the cancellation of a registered brand may only be limited to procedural actions in administrative business such cancellation the brand from the general register and announcing the cancellation the brandin the official news of that brand.